2024
DOI: 10.1186/s11658-023-00523-z
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA-derived small RNA tRF-Glu-CTC attenuates neointimal formation via inhibition of fibromodulin

Qi-Lan Jiang,
Jia-Ying Xu,
Qing-Ping Yao
et al.

Abstract: Neointimal hyperplasia is a pathological vascular remodeling caused by abnormal proliferation and migration of subintimal vascular smooth muscle cells (VSMCs) following intimal injury. There is increasing evidence that tRNA-derived small RNA (tsRNA) plays an important role in vascular remodeling. The purpose of this study is to search for tsRNAs signature of neointima formation and to explore their potential functions. The balloon injury model of rat common carotid artery was replicated to induce intimal hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Endovascular proliferation is a natural repair process after vascular damage, but excessive proliferation can lead to the occurrence of vascular restenosis. Endometrial proliferation of blood vessels originates from the excessive proliferation, migration, and phenotypic transformation of smooth muscle cells in the intima of blood vessels, which are stimulated by local or circulatory oxidative stress and inflammatory factors [ 182 , 183 ]. The entire process includes endothelial damage, platelet aggregation, inflammatory cell infiltration, smooth muscle cell proliferation and migration to the subintima, etc [ 184 ] Endovascular hyperplasia is the central link in the pathological process of vascular remodeling.…”
Section: The Mechanism Of Tongxinluo In Preventing and Treating Cardi...mentioning
confidence: 99%
“…Endovascular proliferation is a natural repair process after vascular damage, but excessive proliferation can lead to the occurrence of vascular restenosis. Endometrial proliferation of blood vessels originates from the excessive proliferation, migration, and phenotypic transformation of smooth muscle cells in the intima of blood vessels, which are stimulated by local or circulatory oxidative stress and inflammatory factors [ 182 , 183 ]. The entire process includes endothelial damage, platelet aggregation, inflammatory cell infiltration, smooth muscle cell proliferation and migration to the subintima, etc [ 184 ] Endovascular hyperplasia is the central link in the pathological process of vascular remodeling.…”
Section: The Mechanism Of Tongxinluo In Preventing and Treating Cardi...mentioning
confidence: 99%
“…The dynamic switching of the VSMC phenotype from contractile to synthetic is a common pathogenesis of various vascular remodeling diseases (VRDs) [ 3 5 ] and is typically characterized by a loss of contractile function, replacement of proproliferative and antiapoptotic factors, and increased secretion of extracellular matrix [ 6 9 ]. In particular, when vascular endothelial damage or postoperative restenosis occurs, an imbalance between excessive VSMC proliferation and insufficient apoptosis may lead to the abnormal accumulation of vascular intimal cells, which can cause atherosclerosis or restenosis [ 10 12 ]. A classic rat model for studying vascular injury has shown that the synthetic peptide MRSP effectively inhibits neointimal hyperplasia by promoting VSMC apoptosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%